Endothelin-1 Regulation of Exercise-Induced Changes in Flow: Dynamic Regulation of Vascular Tone - Rapoport, Robert M.; Merkus, Daphne (Frontiers in Pharmacology, 2017)
Although endothelin (ET)-1 is a highly potent vasoconstrictor with considerable efficacy in numerous vascular beds, the role of ET-1 in the regulation of vascular tone remains unclear. The perspective that ET-1 plays little role in the on-going regulation of vascular tone at least under physiologic conditions is supported by findings that potential ET-1 constriction is minimized by the release of the vasodilator and ET-1 synthesis inhibitor, nitric oxide (NO). Indeed, ET-1 release and constriction is self-limited by ET-1-induced, endothelial ETB receptor-mediated release of NO. Moreover, even if the balance between ET-1 and NO were reversed as the result of lowered NO activity, as occurs in a number of pathophysiologies associated with endothelial dysfunction, the well-known resistance of ET-1 constriction to reversal (as determined with exogenous ET-1) precludes ET-1 in the dynamic, i.e., moment-to-moment, regulation of vascular tone. On the other hand, and as presently reviewed, findings of ET-1-dependent modulation of organ blood flow with exercise under physiologic conditions demonstrate the dynamic regulation of vascular tone by ET-1. We speculate that this regulation is mediated at least in part through changes in ET-1 synthesis/release caused by pulsatile flow-induced shear stress and NO.